Towards technological interventions and their social implications. Similarities between Chandigarh and Lima - Zadel, Vanessa (Universidad de Lima. Carrera de Arquitectura, 2020)
This article presents the possibilities and social impact that technological interventions have in our cities. Common bases for these technological implications include, for example, the fields of IoT solutions, artificial intelligence, smart mobility and integrated waste management solutions. The common foundations of social impact are a powerful tool for the formation of intelligent communities, which can demonstrate equity and accessibility. Therefore, there is a need for spaces for community creators that can help others not only to keep up with technology and use it efficiently but also to connect them with new communities and adapt different solutions to various physical conditions.